Analysis of Yield Potential of Six Strain F7 Generation Rice (Oryza sativa L.) in Medium Plains - Amalina, Hafira Nandyta Nur; Adiredjo, Afifuddin Latif (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2025)
Rice has a very important role for the sustainability of human life, this is because rice is one of the staple foods needed by humans. Based on data from the Central Statistics Agency (2022), rice production in the East Java region has decreased by 102,827.67t compared to rice productivity in 2021. So, to reduce imports is to carry out agricultural intensification, need to get superior varieties. These must through several stages starting from crossing to several stages of selection to get superior lines. These superior strains are then subjected to yield tests before being made into new superior varieties (NSV). The aims of this research were to determine the yields of 6 F7 strain of rice in irrigated lowland areas and their differences with the control varieties, and to obtain the selected F7 strain which had high yield characteristics. The yield component parameters observed included: plant height (cm), number of tillers (sum), number of productive tillers (sum), panicle length (cm), flag leaf shape, 50% dan 100% flowering age (DAP), and harvesting age (DAP), number of grains per panicle (sum), the number of panicles per clump (sum), filled grain (%), 1000 grain weight (g), yield (t/ha), and the difference in yield to the control variety (%). The outcome component parameters and results will then refer to the IRRI Standard Evaluation System of Rice (SES) 2013. The data obtained analyzed using ANOVA and if any significantly different results a further test used the Duncan Multiple Range Test (DMRT) at 5%.